2012
DOI: 10.1352/1934-9556-50.3.251
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Instrument to Measure Medical Students' Attitudes Toward People with Disabilities

Abstract: As curricula to improve medical students' attitudes toward people with disabilities are developed, instruments are needed to guide the process and evaluate effectiveness. The authors developed an instrument to measure medical students' attitudes toward people with disabilities. A pilot instrument with 30 items in four sections was administered to 342 medical students. Internal consistency reliability and factor analysis were conducted. The Cronbach's alpha coefficient was 0.857, indicating very good internal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 30 publications
0
7
0
2
Order By: Relevance
“…Several studies have found that providing specific training to medical students as well as opportunities for them to encounter patients with disabilities yields benefits in terms of improving student's attitudes and comfort level regarding people with disabilities and increasing their knowledge and skills in providing care to these patients (Brown et al 2010;Karl et al 2013;Long-Bellil et al 2011). Few medical schools or residency programs currently offer these kinds of training experiences although this has begun to change (Graham et al 2009;Moroz et al 2010;Symons et al 2009) and research is being conducted to better assess the efficacy of these efforts (Symons et al 2012;Lam et al 2010). Rather than simply adding a single lecture to an existing course, however, medical schools and residency programs must integrate into their curricula required courses and clinical rotations focused on individuals with ASD across the lifespan (McDougle 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that providing specific training to medical students as well as opportunities for them to encounter patients with disabilities yields benefits in terms of improving student's attitudes and comfort level regarding people with disabilities and increasing their knowledge and skills in providing care to these patients (Brown et al 2010;Karl et al 2013;Long-Bellil et al 2011). Few medical schools or residency programs currently offer these kinds of training experiences although this has begun to change (Graham et al 2009;Moroz et al 2010;Symons et al 2009) and research is being conducted to better assess the efficacy of these efforts (Symons et al 2012;Lam et al 2010). Rather than simply adding a single lecture to an existing course, however, medical schools and residency programs must integrate into their curricula required courses and clinical rotations focused on individuals with ASD across the lifespan (McDougle 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These factors were similar to the ones identified in the initial validation of the instrument. 27 Comfortable with interaction Uneasy with interaction; acknowledge negative feelings Comfortable with interaction/integration in general community Conditional comfort Positive impression of self-concepts of people with disabilities Respondents tended to respond consistently to statements regarding comfort level around people with disabilities, and were also consistent in answering ''negative'' statements regarding their perception of people with disabilities feeling sorry for themselves, expecting special treatment, and being resentful, as well as with comfort regarding social situations and behavior. Finally, the statement that ''People with disabilities are as happy as people without disabilities'' appeared to constitute a fifth factor, along with two additional items regarding social comfort around people with disabilities.…”
Section: Resultsmentioning
confidence: 92%
“…27 We developed the instrument by reviewing and adapting existing tools for assessing attitudes toward people with disabilities, 28 as well as from input received from local professionals who work with people with disabilities, medical educators, patients and families. The instrument includes demographics (age and gender), personal and education experience with people with disabilities, 18 attitude/opinion items related to people with disabilities, and reaction to two clinical vignettes (one with a patient with an apparent disability accompanied by a companion, and one with a patient without an apparent disability accompanied by a companion).…”
Section: Measurement Instrumentmentioning
confidence: 99%
“…Una somera revisión de los trabajos publicados recientemente en este ámbito ilustra esta situación. Symons, Fish, McGuigan, Fox y Akl (2012) obtienen una estructura de cinco factores; Morin et al (2013) cinco factores, dos en la dimensión afectiva, dos en la cognitiva y uno en la conductual; Power y Green (2010) cuatro y la presencia de un factor común fuerte; Boo y Nie (2017) revisan y desarrollan el Cuestionario de Actitudes hacia la Discapacidad (Morin et al, 2013) en el contexto asiático, obteniendo una estructura de tres factores. Uno de los denominadores comunes de estos trabajos es que los diferentes métodos de extracción produjeron resultados con un número óptimo de factores que no se confirmaron posteriormente o cuyos ajustes fueron precarios al ser sometidos a análisis factorial confirmatorio.…”
unclassified
“…Uno de los denominadores comunes de estos trabajos es que los diferentes métodos de extracción produjeron resultados con un número óptimo de factores que no se confirmaron posteriormente o cuyos ajustes fueron precarios al ser sometidos a análisis factorial confirmatorio. Así, Symons et al (2012) obtienen inicialmente una estructura con seis factores atendiendo a la regla de Kaiser-Guttman (valores propios > 1) (Guttman, 1954) y de cuatro factores mediante análisis paralelo de Horn (Horn, 1965). Boo y Nie (2017) obtuvieron soluciones iniciales de siete y cuatro factores, aplicando la regla de Kaiser-Guttman y el análisis del gráfico de sedimentación (Cattell, 1966), respectivamente.…”
unclassified